Federal Population Register: Experience in Management of Information Resources in Russian Federation - Olga V. ZAKHARCHENKO; Anton K. KUZNETSOV (Communications of International Proceedings, 2021)
One of the priority tasks of the state in complex modern circumstances is improve the mechanisms for the implementation of state and municipal services, decline in document management, optimize government tasks and functions, enhance the effectiveness of management decisions. This study examines the issues of optimizing the information support of the state on creating information system for registering the population – Unified federal information register, that contains information about population of Russian Federation. Primary goals, the procedure and mechanism of formation, the sources of the federal register of information about population, as well as the purposes of use are considered. Special attention is given to the problems of information security. Recommendations for further improvement of the legal regulation of the maintenance and usage of the federal population register are presented.
Keywords: Federal register; information system; database; resource; population data; personal data.